Caso Electroencefalográﬁco - Velon,Ana Graça (2010)
Introduction. Eyelid myoclonia with or without absences may occur in several epileptic conditions, and they are frequently misinterpreted as movement disorders. Case report. A seven-year-old boy was admitted for evaluation of eye blinking that started at age of six. He had never had generalized tonic-clonic or absence seizures. Video-EEG monitoring revealed 3-5 Hz irregular occipital or generalized polyspike and polyspike-wave complexes, precipitated by eye closure. They were accompanied by eye-lid myoclonia. Photic stimulation induced photoparoxysmal response. Brain MRI was normal. He was initially treated with clobazam and then levetiracetam with no response. Valproate was added with control of the symptoms. Conclusion. Eyelid myoclonia without absences are often difﬁcult to classify. Video-EEG may help to clarify these cases.